Dirty floating and monetary independence in Central and Eastern Europe - The role of structural breaks - Thomas Windberger; Jesus Crespo Cuaresma; Janette Walde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
Obtaining reliable estimates of the volatility of interest rates and exchange rates is a necessary condition to evaluate issues related to monetary independence and fear of floating. In this paper we use methods which explicitly account for structural breaks in the volatility dynamics in order to assess monetary independence in the Czech Republic, Hungary and Poland. Our results indicate that the explicit modelling of structural breaks in volatility estimates can lead to striking differences concerning the evidence of monetary independence in Central and Eastern Europe. The results based on volatility estimates which account for regime change tend to indicate that the Czech Republic, Hungary and Poland have had a significant degree of monetary independence in the last decade.
Keywords: F31; C22; C11; 330; Fear of floating; monetary independence; structural break; change-point model